PENGARUH KEPEMILIKAN KELUARGA DAN KARAKTERISTIK KOMITE AUDIT TERHADAP MANAJEMEN LABA - Dwiyanti, Kadek Trisna; Astriena, Meyta (Universitas Airlangga, 2018)
This study aims to examine the effect of family ownership and audit committee characteristics on earnings management. The independent variables in this study are family ownership, audit committee size, accounting expertise of audit commitee, and audit committee's number of meetings. Earnings management as a dependent variable is measured by discretionary accrual as a proxy of earnings management. This study also uses leverage and size as control variables.The sample of this study are 81 manufacturing companies listed on Indonesia Stock Exchange (IDX) with data for a period of 2 years (2015-2016). Using multiple linear regression, this study finds family ownership, audit committee size, accounting expertise of audit committee and audit committee's number of meetings have a negaticve effect on earnings management.This study contributes to the existing literature by providing new result related to the influence of family ownership and audit committee characteristics on earnings management practice. In addition, this study offer some useful insights for policy maker in determining the most effective policy to reduce earnings management.